ANALISIS PENGUNGKAPAN ANTI-KORUPSI DAN PRAKTIK ETIS DALAM LAPORAN KEBERLANJUTAN PT TELKOM INDONESIA TAHUN 2023 BERDASARKAN GRI STANDARD 2021 - faiza, nur; Novia Oktaviani Febrilia; Maria Yovita R Pandin (Universitas Prof.Hazairin,SH Bengkulu, 2024)
This research aims to analyze anti-corruption disclosures and ethical practices in PT Telkom Indonesia (Persero) Tbk's sustainability report based on the 2021 GRI Standard. By using a qualitative approach and case study design, this research aims to understand the effectiveness of implementing these standards in the company's ethical practices. The results show that PT Telkom Indonesia (Persero) Tbk has a significant commitment to anti-corruption, including Business Integrity training for all new employees and proactive corruption risk assessments. There were no confirmed incidents of corruption throughout 2023, reflecting the effectiveness of the internal control and training systems implemented. In addition, disclosing ethical values ​​in the company's vision and mission shows that ethical practices are an integral part of the company's culture. Telkom's commitment to non-discrimination can also be seen from the absence of incidents of discrimination and employee protection policies. Overall, this research indicates that PT Telkom Indonesia (Persero) Tbk has implemented transparent and responsible business practices, in line with the sustainability principles promoted by GRI.